Knowledge and Attitude of Sunscreen Usage in Indonesia: A Systematic Review of Observational Studies - Made Indira Dianti Sanjiwani; I Putu Hendri Aryadi (Berkala Ilmu Kesehatan Kulit dan Kelamin, 2026)
Background: Chronic excessive ultraviolet (UV) exposure may cause damage the skin both structurally and functionally. Protection from sunlight is essential to do, one of which is the use of sunscreen. Knowledge and attitudes toward the use of sunscreen in the prevention of skin cancer are important to note. A few studies have investigated sunscreen knowledge and practice in Indonesia; however, to date, no research has compiled data from various regions of the country. It aims to summarize the findings about knowledge and attitude toward sunscreen usage in the published research studies conducted Indonesia. Review: We searched for published literature in English and Indonesian from 2013-2023. We included all studies that assessed the knowledge and practice of using sunscreen in Indonesia. Our search identified 1455 studies, 11 of which included 1843 participants in this systematic review. Based on gender, it was found that there are more female respondents than male respondents. The pooled percentage on the level of knowledge in good, moderate, and poor categories is 42.9%, 44.3%, and 12.8, respectively. Meanwhile.9% had good practices, 32.9% had poor practices, and 28.2% had moderate practices. Conclusion: Knowledge related to sunscreen is obtained generally at a moderate level while the practice of using sunscreen is obtained varies between good, moderate, and poor.